صحابیات ؓکے اسلوبِ دعوت وتربیت میں انسانی نفسیات کا لحاظ :عصر حاضر کے تناظر میں ایک مطالعہ: Keeping in view the Human Psychology in the Style of Dawah and Education by Ṣahābiāt: A Study in the Context of Present age (Al-Qamar, 2023)
Islam is a comprehensive and universal religion that has been granted through Hazrat Muhammad (PBUH); the last messenger of ALLAH. Its beauty lies in the fact that the preaching of Islam will continue until the day of Resurrection. After the demise of Holy Prophet (PBUH), it is incumbent upon every Muslim man and woman to play their part in preaching of this religion. A society can only be reformed when there are people who encourage good deeds and prevent others from evil deeds. If we take a look at the efforts of today’s Muslims for Islam, we find men working for the cause to some extent but women are almost none. In fact, today, women are greater in number as compared to men in past, which is why they need to work even more in this domain. While the women who were educated are trained in the company of Holy Prophet (PBUH), played a vital role in this sector. Knowledge about the core concepts of Islam, domestic life and intricate problems related specifically to women came only through the mothers of the Believers (Ummahat ul momimeen) and their Companions (Sahabiyaat), but today’s women have left this field empty. The few women who are working for the cause mostly emphasize on preaching and training without knowing the psychology of their audience, which causes harm instead of benefit. Therefore, this research paper will discuss that how the female companions of prophet Muhammad (PBUH); i.e. Sahabiyaat, used to preach and train listeners keeping in view the psychological aspects of audience and because of this wise approach, they were immediately ready to act. The fact that how by adopting the said method, today’s society can be reformed, will also be discussed in this paper.
Keywords: Ṣahābiāt; Human Psychology; Dawah; Education; Style; Study; Context; Present age